EFEKTIVITAS SPLINT DAN LATIHAN MOBILISASI UNTUK MENGURANGI SKALA KEPARAHAN GEJALA PADA CARPAL TUNNEL SYNDROME : Literature Review - Nida Mawaddah (2020)
Background: Carpal tunnel syndrome is a syndrome that occurs in the wrist due to the presence of compression in the median nerve through the carpal tunnel. Someone who has carpal tunnel syndrome will generally experience symptoms, such as parastheses in the fingers, pain especially at night and a tingling sensation in the thumb, index finger and middle finger, even these symptoms can affect the functional activity of patients. Purpose: This review aims to examine existing literature in order to be able to obtain specific results regarding the effectiveness of splint and mobilization exercises to reduce symtoms severity scale in the cases of carpal tunnel syndrome. Method: the method used is literature review, searching using pubmed, google scholar and science direct by entering the established criteria and using PICO analysis, the results obtained are 6 appropriate journals, namely 5 randomized controlled trial journals and 1 quasi-experimental journal. Results: The parameters used as an example of the Boston Carpal Tunnel Syndrome Questionnaire (BCTSQ), while for the quality of the assessment using the Evidance Database Physiotherapist (PEDro), obtained quality results from 4 to 8 Reducing the scale of the severity of the effect by using the Boston Carpal Tunet Syndrome Questionnaire, but if combination with other combinations the results obtained will be more optimal Keywords: Carpal Tunnel Syndrome, Splint, Mobilization Exercise, Symptoms Severity Scale